(untitled) (Revista Peruana de Investigación Educativa, 2022)
This research was conducted under the qualitative paradigm and aimed to know the attributions that cause success and failure in thesis elaboration of students in clinical, educational and social psychology at a private university in Lima - Peru. Data was collected with a semi-structured interview and then results were validated with participants. The thesis advisor is the main reason identified by the participants in this study to explain their results in thesis course, followed by their role as thesis students or the features that a thesis student should have, such as enjoyment and interest in different parts of an investigation and value level in thesis elaboration. Other attributions were the ability, resource management, personal characteristics, etc. In addition, we explored the process that generates a causal attribution and emotions caused by experiences of students in the elaboration of their thesis, where highlight the happiness and frustration.